Automated Scoring of Speaking and Writing: Starting to Hit its Stride - Jones, Daniel Marc; Cheng, Liying; Tweedie, M. Gregory (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
This article reviews recent literature (2011–present) on the automated scoring (AS) of writing and speaking. Its purpose is to first survey the current research on automated scoring of language, then highlight how automated scoring impacts the present and future of assessment, teaching, and learning. The article begins by outlining the general background of AS issues in language assessment and testing. It then positions AS research with respect to technological advancements. Section two details the literature review search process and criteria for article inclusion. In section three, the three main themes emerging from the review are presented: automated scoring design considerations, the role of humans and artificial intelligence, and the accuracy of automated scoring with different groups. Two tables show how specific articles contributed to each of the themes. Following this, each of the three themes is presented in further detail, with a sequential focus on writing, speaking, and a short summary. Section four addresses AS implementation with respect to current assessment, teaching, and learning issues. Section five considers future research possibilities related to both the research and current uses of AS, with implications for the Canadian context in terms of the next steps for automated scoring.